Experience of risk management implementation in hygiene and labour safety and possibility of its implementation at forestry units in Ukraine - Gilpert, V.V. (Forestry, Forest, Paper and Woodworking Industry, 2018)
The world experience of level minimization for workplace injuries and professional diseases is considered. The prospective of risk-oriented approach principles implementation into the national legislation in the field of labour safety are pointed out. It is highlighted that the system of labour safety and risk management implemented in 2015 in forestry has become a new turn to the modern approaches to transform the system of labour safety management at forestry units. The range of measures is proposed to support the certification of systems of hygiene and labour safety management in accordance with the new standard ISO 45001.